Circular economy and smart specialisation business strategies: the Dnipropetrovsk region case - Olena Churikanova; Daria Pilova; Benito Giordano; Leonardo Piccinetti; Mauro Amoruso (Insights into Regional Development)
This article explores the integration of the circular economy in Ukraine's smart specialisation strategies, focusing on a case study of the Dnipro Region. Investigating the symbiotic relationship between these concepts delves into legal aspects and presents an overview of Dnipro's unique economic characteristics. The case study illustrates the city's potential to use the smart specialisation approach to enhance economic growth. Utilising correlation regression analysis, it assesses the region's readiness for circular economy principles. Global case studies offer insights for Dnipro, and a SWOT analysis guides policymakers. In conclusion, the article provides a roadmap for harmoniously integrating circular economy principles and smart specialisation to future-proof Ukraine's regional development trajectories.